Appearance of Epic and Novel in Kurdish literature, imitation or philosophical Appearance - Ameen, Sirwan J.; Mohammd, Sangar Q. (Humanities Journal of University of Zakho, 2018)
We divided this research into two main sections. The first section consists of three small parts. In the first part we talked about concept of philosophy. We spoke about any thought or idea that has its place in general philosophy. Appearance of epic and its relationship with general philosophy is the second part in the first main part in this research. The third part is about appearance of Kurdish epic. The second section consists of three different parts. In the first part we talked about individual philosophy. Second part was place of speaking about appearance of novel inside European societies, and how these societies helped novel to arise. In the third part in section two we focused on Kurdish novel and its relationship with individualism. Also we tried to answer this question, is individualism made Kurdish novel to be appeared or Kurdish novel is just imitation of European novel?